Modeling and simulation of three phase controlled rectifier / Ridwan Mokhtar - Mokhtar, Ridwan (2011)
In this project, an AC - DC converter which controlled by using PWM switching technique, is developed. Switching strategy and operational principles of the proposed rectifier are explained and operational topologies are respectively given. The performance of the three phase controlled rectifier is evaluated by using simulation model rectifier is built in MATLAB Simulink and PSpice software, a specially designed software package for power electronic simulation. The simulation results are presented and discussed. Various tests by using difference carrier frequency are performed to investigate the actual performance of the rectifier. MATLAB SIMULINK results are compared with the well-known PSpice simulations to ascertain the accuracy of modeling.